EFFECT OF METHYLENE−BLUE ON THE VASODILATOR ACTION OF INHALED NITRIC−OXIDE IN HYPOXIC SHEEP - Young, J; Dyar, O; Xiong, L; Zhang, J; Gavaghan, D (1994)
We have examined the effect of methylene blue 4 mg kg(-1) on the pulmonary vasodilator action of inhaled nitric oxide (8, 32, 128 and 512 volumes per million) in nine sheep with pulmonary hypertension induced by hypoxia (Fl(o2) = 0.12). The dose-response to nitric oxide was unchanged by methylene blue, but increased cardiac output was noted (P andlt; 0.01). These results indicate that methylene